Typification of three names in the genus Knautia (Caprifoliaceae; Dipsacoideae) - Ferrer Gallego, Pedro Pablo; Fabado, Javier (Mediterranean Botany, 2022)
The typification of the names Trichera subscaposa var. rupicola, T. subscaposa var. macrotrycha, and Knautia subscaposa var. subintegerrima is discussed. The names are lectotypified using specimens preserved in the Willkomm Herbarium at COI, Carlos Pau Herbarium at MA, and Rouy Herbarium at LY, respectively.